Costs of Farmland Fragmentation: Evidence from Farmland Transactions in Eastern Germany - Lars Isenhardt; Stefan Seifert; Theelke Wiltfang; Silke Hüttel (German Journal of Agricultural Economics)
Farmland fragmentation in use is related to higher operation cost and reduced productivity, while ownership fragmentation increases transaction costs, both leading to inefficient land use and diminished overall farm performance. This paper aims to quantify the costs of farmland ownership fragmentation using a market-based approach. We hypothesize that buyers and sellers in the farmland market have a lower valuation and demand for spatially separated farmland. To test this hypothesis, we analyze a rich dataset of 24,528 arable land transactions from the eastern German Federal State of Brandenburg from 2000 to 2022 that includes information on whether the traded land was spatially fragmented. Using a doubly robust approach combining matching and regression, we find that package transactions of spatially separated parcels achieve on average 6.7% lower prices than transactions of single parcels with the same size and comparable characteristics. The quantified markdown for packages suggests that market participants associate costs with fragmentation and consider these into their valuation for farmland.